Reaktualisasi Pengamalan Nilai Pancasila untuk Demokrasi Indonesia - Mutiani Mutiani (Sosio-Didaktika: Social Science Education Journal, 2015)
Pancasila as an integral (comprehensively) is a solid supporting to the state established in Indonesia. Pancasila is maintained and developed with the aim to protect and develop the dignity and rights of all citizens of the nation to democracy in Indonesia. Posts in this article aims to explain how the urgency of re-actualization of Pancasila. As a method of this paper is literature study. The writer was conducting Pancasila in the context of political education in Indonesia emphasis on understanding the unity and integrity of the nation and the values listed in UUD 1945 with its main foundation of Pancasila. As the result, therefor, Pancasila is expected to realize the Good and Smart Citizenship, which, law-abiding citizens, to the literacy of citizens to political issues. Permalink/DOI: http://dx.doi.org/10.15408/sd.v2i2.2822